Macro stress testing euro area banks' fees and commissions - Christoffer Kok; Harun Mirza; Cosimo Pancaro (European Central Bank (ECB), 2017)
This paper uses panel econometric techniques to estimate a macro-financial model for fee and commission income over total assets for a broad sample of euro area banks. Using the estimated parameters, it conducts a scenario analysis projecting the fee and commission income ratio over a three years horizon conditional on the baseline and adverse macroeconomic scenarios used in the 2016 EU-wide stress test. The results indicate that the fee and commission income ratio is varying in particular with changes in its own lag, the shortterm interest rate, stock market returns and real GDP growth. They also show that the fee and commission income ratio projections are more conservative under the adverse scenario than under the baseline scenario. These findings suggest that stress tests assuming scenario-independent fee and commission income projections are likely to be awed.
Keywords: G21; G17; G01; 330; fee and commission income; stress testing; scenario analysis